2017
DOI: 10.1016/j.bone.2017.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo construction of human primary 3D–networked osteocytes

Abstract: A human bone tissue model was developed by constructing ex vivo the 3D network of osteocytes via the biomimetic assembly of primary human osteoblastic cells with 20–25 µm microbeads and subsequent microfluidic perfusion culture. The biomimetic assembly: (1) enabled 3D-constructed cells to form cellular network via processes with an average cell-to-cell distance of 20–25 µm, and (2) inhibited cell proliferation within the interstitial confine between the microbeads while the confined cells produced extracellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 46 publications
3
39
0
Order By: Relevance
“…The OB proliferated after three weeks in culture and secreted a mineralized extracellular matrix, the cells being inter-connected through dendritic processes and gap junctions, as previously described in literature [45][46][47]. This network of OB could constitute the premise for early differentiation of these cells grown onto the surfaces of BHA and BHA:LiP coatings in vitro and, consequently, for a better osteointegration in vivo [48,49]. This is in line with other studies showing that primary human osteoblastic cells were enabled to produce extracellular matrix and form an ex vivo 3D network of osteocytes, which are the terminally differentiated bone cells, via biomimetic assembly using microfluidic perfusion culture [48].…”
Section: Structural Morphology Of Obsupporting
confidence: 69%
See 1 more Smart Citation
“…The OB proliferated after three weeks in culture and secreted a mineralized extracellular matrix, the cells being inter-connected through dendritic processes and gap junctions, as previously described in literature [45][46][47]. This network of OB could constitute the premise for early differentiation of these cells grown onto the surfaces of BHA and BHA:LiP coatings in vitro and, consequently, for a better osteointegration in vivo [48,49]. This is in line with other studies showing that primary human osteoblastic cells were enabled to produce extracellular matrix and form an ex vivo 3D network of osteocytes, which are the terminally differentiated bone cells, via biomimetic assembly using microfluidic perfusion culture [48].…”
Section: Structural Morphology Of Obsupporting
confidence: 69%
“…This network of OB could constitute the premise for early differentiation of these cells grown onto the surfaces of BHA and BHA:LiP coatings in vitro and, consequently, for a better osteointegration in vivo [48,49]. This is in line with other studies showing that primary human osteoblastic cells were enabled to produce extracellular matrix and form an ex vivo 3D network of osteocytes, which are the terminally differentiated bone cells, via biomimetic assembly using microfluidic perfusion culture [48]. Chen et al [49] reported on mineralized matrix morphology in 3D culture of osteoblasts and revealed by SEM a synergistic cross-talk between 1alpha, 25 (OH) 2 vitamin D3, and bone morphogenetic protein-2 that sustained improved osteogenesis and mineral deposition.…”
Section: Structural Morphology Of Obmentioning
confidence: 99%
“…The low quantity needed for bone-on-a-chip experiments and the stability in the expression of the most critical genes during in vitro culture (Sun et al, 2017) favored the choice of primary human osteoblasts (HOBs) for the bone tissue model presented in this study.…”
Section: Cell Culturementioning
confidence: 99%
“…However, osteoblasts can have three other possible fates but the mechanism regulating this transition is not clearly understood yet: they can become bone-lining cells (inactive osteoblasts), undergo apoptosis, or transdifferentiate into chondroid-depositing cells (Dallas and Bonewald, 2010). Gene expression profiles (Boukhechba et al, 2009;Sun et al, 2017) and immunohistochemistry stainings (Uchihashi et al, 2013;Sun et al, 2015;McGarrigle et al, 2016) in traditional 3D culture systems showed that the expression of osteoblast and osteocyte markers in vitro corresponded to the in vivo expression at the same differentiation stages (Franz-Odendaal et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Ex vivo bone explants have the advantage of allowing the study of living osteocytes within their natural setting and are particularly well suited to investigating the response to mechanical loading (Kogawa et al 2018, Morrell et al 2018. More recently, advances have been made in the 3D culture of osteocytes using biomimetic assemblies, which allow formation of an inter-osteocyte connection network that replicates mechanostransduction responses (Sun et al 2017(Sun et al , 2018. Since sclerostin expression is regulated by mechanical loading, access to such systems, which more faithfully reproduce the osteocyte's native environment, will prove highly useful in the future.…”
Section: Osteoblast Lineagementioning
confidence: 99%